Fuzzy Logic Based Harmonic Elimination in Single Phase Inverters - Duranay, Zeynep Bala; Guldemir, Hanifi (Ieee, 2017)
A fuzzy system for the elimination of specific low order harmonics in the output voltage of single phase inverters is proposed. The proposed system does not need look up tables which require much memory as in traditional methods and no need for training which takes much time as in neural networks. Here, modulation index is used as input to fuzzy system and switching signals are generated. Predetermined low order harmonics are successfully eliminated.
26th International Scientific Conference on Electronics (ET) -- SEP 13-15, 2017 -- Sozopol, BULGARIA
Keywords: Fuzzy Logic; Harmonic analysis; Harmonic elimination; Inverter; Pulse width modulation